Who Talked about What Regarding Derek Chauvin's Trial: A Work‐In‐Progress Analysis. Issue 1 (14th October 2022) - Duan, Yiran; Hemsley, Jeff; Smith, Alexander O.; Gray, LaVerne; Gandhi, Dhwani
ABSTRACT: This work‐in‐progress study investigates the information sharing behavior of different levels of Twitter influencers within the context of the #BlackLivesMatter social movement and its related discussions #AlllivesMatter and #BlueLivesMatter during the 2‐week period around Derek Chauvin's trial. Using qualitative content analysis and quantitative machine learning methods, we analyzed over one million retweets to test if different levels of influencers tend to spread different kinds of information in the discussions around #All/Black/BlueLivesMatter on Twitter. We found out that different levels of influencers tend to spread different information within and between the #All/Black/BlueLivesMatter, and we offer some explanations through the lens of curation logics. We suggest that different levels of influencers may be exposed to different incentives, and be facing different social norms, which leads to different information behaviors. This work‐in‐progress study contributes to updating the theory of curated logics, virality, and influencers, as well as provides empirical data for the discussions of the #BlackLivesMatter social movement and its related discussions of #AllLivesMatter and #BlueLivesMatter.